Analysis of Mathematics Learning Difficulties Among 8th-Grade Students at SMP Unimuda Pulau Arar - Fenetiruma, Gilda Leonora; Dwi Pamungkas; Henny Ari Astutik (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to determine and describe the learning difficulties experienced by class VIII students of SMP Unimuda Pulau Arar in learning mathematics. This study uses a descriptive qualitative method. The subjects in this study were 3 class VIII students of SMP Unimuda Pulau Arar. Data collection techniques in this study were observation, tests, questionnaires, and interviews. Data analysis in this study used the Miles and Huberman data analysis technique. To obtain data validity, researchers conducted a credibility test with the triangulation technique. The results of the analysis in this study indicate that there are three categories of students who experience difficulties in learning mathematics, namely students with high, medium and low learning difficulties. Students with high learning difficulties have the characteristics of experiencing obstacles in understanding concepts, following instructions, and submitting assignments on time. They are easily distracted, even though they show good self-confidence when working on problems. Students with moderate learning difficulties have the characteristics of needing additional time to understand abstract concepts. In contrast, students with low learning difficulties generally meet the learning difficulty indicators with more consistent results